Diamonds in the rough - searching for high potential in youth table tennis players - Faber, I. R. (2016)
The aim of this thesis is to gain insight into the concept of high potential for elite performance in table tennis by searching and assessing personal talent determinants in youth players (6-12 years). In chapter 2, a research proposal including theoretical considerations is presented, which is used for the design of the studies conducted as part of this thesis. Both top-down (quantitative) and bottom-up (qualitative) methods are described for the purpose of this thesis. In chapter 3, a systematic review presents a theoretical framework and a state-of-the-science overview on the instruments available in racquet sports to assess personal talent determinants in youth players. Special attention is paid to the validity of these instruments for talent developmental purposes. Chapter 4 through 8 describe the development and evaluation of a perceptuo-motor skills assessment to measure perceptuo-motor skills in youth table tennis players (6-12 years) as a part of a talent development programme. The reproducibility, the ability to discriminate between high potential players and others and the predictive value of the assessment are evaluated. Chapter 4 is based on data from 1998-2013 to evaluate the predictive value of the four test items of the motor skills assessment that were used throughout this period. Chapter 5 presents the study on the development of a new eye hand coordination test. Chapter 6 contains the first evaluation of the motor skills assessment consisting of eight test items, including an analysis regarding the reproducibility per test item, internal consistency, latent variables (principal component analysis) and concurrent validity. In chapter 7 a study on the reproducibility and discriminative validity of two revised test items is reported. Chapter 8 contains an observational prospective study to provide an evaluation of the predictive value of the current motor skills assessment. As the configuration of `high potential` had to be unravelled further, chapter 9 describes a qualitative study in which hidden knowledge regarding this topic from elite players and their youth trainers was uncovered. The findings of this study give directions for further studies on `high potential` in sports. In chapter 10, the findings of the included studies are combined into a general discussion. This chapter also contains the main conclusions and directions for professionals and scientists for future research and practice, respectively